Racism and prejudice in digital social networks: research with high school students - de Paulo, Rodrigo Barbosa [UNESP]; Casarin, Helen de Castro Silva [UNESP]; Castanha, Rafael Gutierres [UNESP]; Bastos, Glória Maria Lourenço (Universidade Federal de Santa Catarina (UFSC), 2022)
Objective: Discuss how prejudice has been evidenced in digital social networks, with an emphasis on racism; identify the main prejudices suffered and witnessed by Brazilian high school students in digital social networks. Method: The theoretical foundation was built from the dialogue of black authors who discuss the topic. The study was carried out in a private school in a city in the interior of the state of São Paulo. For data collection, an electronic questionnaire was applied to the group of high school students at the school. 215 students participated in the research. Result: it appears that most students have social networks and also witness situations of prejudice on the internet, largely due to: color or race, physical appearance, liking people of the same sex and being a woman. It is easier for students participating in the research to perceive the prejudice suffered by others, rather than by themselves. Conclusions: The main conclusion is that, just like in the analog world, educators, including librarians, need to strongly guide the themes related to prejudice and racism in their educational practice in a critical way. It is hoped that the results can be used as a subsidy for the preparation of digital literacy programs for high school students.
RACISMO E PRECONCEITO NAS REDES SOCIAIS DIGITAIS: PESQUISA COM ESTUDANTES DO ENSINO MÉDIO
Keywords: Digital literacy; High school students; Preconception; Racism; Social networks